ZNF148 inhibits HBV replication by downregulating RXRα transcription - Xinyan Yao; Kexin Xu; Nana Tao; Shengtao Cheng; Huajian Chen; Dapeng Zhang; Minli Yang; Ming Tan; Haibo Yu; Peng Chen; Zongzhu Zhan; Siyi He; et al. (Virology Journal, 2024)
Abstract Background Progressive hepatitis B virus (HBV) infection can result in cirrhosis, hepatocellular cancer, and chronic hepatitis. While antiviral drugs that are now on the market are efficient in controlling HBV infection, finding a functional cure is still quite difficult. Identifying host factors involved in regulating the HBV life cycle will contribute to the development of new antiviral strategies. Zinc finger proteins have a significant function in HBV replication, according to earlier studies. Zinc finger protein 148 (ZNF148), a zinc finger transcription factor, regulates the expression of various genes by specifically binding to GC-rich sequences within promoter regions. The function of ZNF148 in HBV replication was investigated in this study. Methods HepG2-Na+/taurocholate cotransporting polypeptide (HepG2-NTCP) cells and Huh7 cells were used to evaluate the function of ZNF148 in vitro. Northern blotting and real-time PCR were used to quantify the amount of viral RNA. Southern blotting and real-time PCR were used to quantify the amount of viral DNA. Viral protein levels were elevated, according to the Western blot results. Dual-luciferase reporter assays were used to examine the transcriptional activity of viral promoters. ZNF148’s impact on HBV in vivo was investigated using an established rcccDNA mouse model. Results ZNF148 overexpression significantly decreased the levels of HBV RNAs and HBV core DNA in HBV-infected HepG2-NTCP cells and Huh7 cells expressing prcccDNA. Silencing ZNF148 exhibited the opposite effects in both cell lines. Furthermore, ZNF148 inhibited the activity of HBV ENII/Cp and the transcriptional activity of cccDNA. Mechanistic studies revealed that ZNF148 attenuated retinoid X receptor alpha (RXRα) expression by binding to the RXRα promoter sequence. RXRα binding site mutation or RXRα overexpression abolished the suppressive effect of ZNF148 on HBV replication. The inhibitory effect of ZNF148 was also observed in the rcccDNA mouse model. Conclusions ZNF148 inhibited HBV replication by downregulating RXRα transcription. Our findings reveal that ZNF148 may be a new target for anti-HBV strategies.